Desarrollo de habilidades de regulación emocional por medio de la herramienta tour de las emociones en niños de primaria de una Institución Educativa Distrital de la ciudad de Barranquilla (2022)
Emotional education in children enhances the recognition of an emotion, through a gesture or an action. That is to say, a visualization of emotional manifestations expressed through words, smiles, tones and accentuations, facial and body expressions is achieved, it should be clarified that this does not allude to the fact that children will become experts in analyzing a person, if not , which will develop in them the basic essential skills for a correct management of emotions at an early age, will encourage the use of self-control skills and, finally, will improve the quality of life. Aguaded & Pantoja (2015), state that the complexity of the human being is not resolved by enhancing only their academic and intellectual capacities, but by developing other skills that enable them to develop as a person. The objective of this project is to propose the Tour de las emociones work tool, which is designed to promote the development of emotional skills in children, managing to visualize the usefulness of the instrument as a pattern to promote emotional regulation. The research is based on the quasi-experimental methodology, since during the implementation of the tool we worked with two groups (control and experimental) where results of advances in the emotional quotient of the students who had access to the tool were obtained much faster than the group that did not have access to it; denoting the usefulness of this instrument as a method of emotional development.